Impact of Resilience on Psychological Well-Being - Niyazova, Adina; Madaliyeva, Zabira (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: The issue of the individual's psychological well-being is one of the most interesting and relevant in psychology. Its study has implications not only for theoretical but also for many of the present practical challenges. This study explores predictors of psychological well-being, one of which is resilience. Objective: The purpose of the study is to analyse psychological well-being predictors and prove that resilience is one of its important predictors. Methods: To achieve the aim, a theoretical grounding of the key concepts was made, and an empirical study was carried out. The following techniques were used: the Ryff Scales of Psychological Well-Being, the Freiburg Personality Inventory and the Maddi's Hardiness Survey. Furthermore, at the empirical level, the characteristics of resilience among different age groups were recorded. Results: The study presents the results of a survey involving 150 people of different ages related to the profession of consulting psychologists. Furthermore, the study identified the following predictors of psychological well-being: resilience, femininity/masculinity, positive attitudes, emotional lability, irritability, and aggression. Conclusions: Based on the study of psychological and pedagogical literature and the study findings, it has been concluded that resilience should be considered a mechanism for achieving psychological well-being. The theoretical analysis described the concepts of "psychological well-being" and "resilience", providing their characteristics and factors.